Digital urban modeling and simulation - Arisona, Stefan Müller; Aschwanden, Gideon; Halatsch, Jan.; Wonka, Peter (Heidelberg : Springer, 2012)
This book is thematically positioned at the intersections of Urban Design, Architecture, Civil Engineering and Computer Science, and it has the goal to provide specialists coming from respective fields a multi-angle overview of state-of-the-art work currently being carried out. It addresses both newcomers who wish to obtain more knowledge about this growing area of interest, as well as established researchers and practitioners who want to keep up to date. In terms of organization, the volume starts out with chapters looking at the domain at a wide-angle and then moves focus towards technical viewpoints and approaches -- P. 4 of cover.
A planning environment for the design of future cities / Gerhard Schmitt -- Calculating cities / Bharat Dave -- The city as a socio-technical system: a spatial reformulation in the light of the levels problem and the parallel problem / Bill Hillier -- Technology-augmented changes in the design and delivery of the built environment / Martin Riese -- City introduction: a model for fomulating, generating, and evaluating urban designs / José P. Duarte, José N. Beirão, Nuno Montenegro and Jorge Gil -- Sortal grammars for urban design: a sortal approach to urban data modeling and generation / Rudi Stouffs, José N. Beirão and José P. Duarte -- Sort machines / Thomas Grasl and Athanassios Economou -- Modeling water use for sustainable urban design / Ramesh Krishnamurti, Tajin Biswas and Tsung-Hsien Wang -- Simulation heuristics for urban design / Christian Derix, Åsmund Gamlesæter, Pablo Miranda, Lucy Helme and Karl Kropf -- Running urban microsimulations consistently with real-world data / Gunnard Flötteröd and Michel Bierlaire -- Urban energy flow modelling: a data-aware approach / Diane Perez and Darren Robinson -- Interactive large-sclae crowd simulation / Dinesh Manocha and Ming C. Lin -- An information theoretical approach to crowd simulation / Cagatay Turkay, Emre Koc and Selim Balcisory -- Intergrating urban simulation and visualization / Daniel G. Alaga -- Visualization and decision support tools in urban planning / Antje Kunze, Remo Burkhard, Serge Gebhardt and Bige Tuncer -- Spatiotemporal visualisation: a survey and outlook / Chen Zhong, Tao Wang, Wei Zeng and Stefan Müller Arisona -- Multi-touch wall displays for informational and interactive collaborative space / Ian Vince McLoughlin, Li Ming Ang and Wooi Boon Goh -- Testing guide signs' visibility for pedestrians in motion by an immersive visual simulation system / Ryuzo Ohno and Yohei Wada.
Includes bibliographical references and author index.
ARC
Keywords: City planning -- Computer simulation; City planning -- Data processing; City planning -- Computer simulation; City planning -- Data processing; Architektur; CAD; Computerkartographie; Computersimulation; Computerunterstütztes Verfahren; Stadtplanung